2004
DOI: 10.1152/ajprenal.00383.2003
|View full text |Cite
|
Sign up to set email alerts
|

Luminal flow induces eNOS activation and translocation in the rat thick ascending limb. II. Role of PI3-kinase and Hsp90

Abstract: Endothelial nitric oxide synthase (eNOS) regulates NaCl absorption by the thick ascending limb of the loop of Henle (THAL). We found that augmenting luminal flow induces eNOS activation and translocation to the apical membrane of THALs (Ortiz PA, Hong NJ, and Garvin JL. Am J Physiol Renal Physiol 287: F274 -F280, 2004). In other cells, eNOS activation by shear stress is mediated by phosphatidylinositol 3-OH kinase (PI3)-kinase. We hypothesized that luminal flow induces eNOS activation via PI3-kinase. Pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 62 publications
1
42
0
Order By: Relevance
“…Previous reports from this group, as well as the present study, implicate NOS3 translocation and phosphorylation 9 at different regulatory sites as important regulators of THAL NOS3 activity. In a recent study, Ortiz et al 33 showed that NOS3 is activated when it localizes to the apical membrane of the THAL. Whether changes in NOS3 phosphorylation and enzyme expression are cytosolic intermediates necessary for the trafficking process is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports from this group, as well as the present study, implicate NOS3 translocation and phosphorylation 9 at different regulatory sites as important regulators of THAL NOS3 activity. In a recent study, Ortiz et al 33 showed that NOS3 is activated when it localizes to the apical membrane of the THAL. Whether changes in NOS3 phosphorylation and enzyme expression are cytosolic intermediates necessary for the trafficking process is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the proteins that interact with NOS have been localized to the kidney; 34 however, its role in the regulation of THAL NOS3 has not been thoroughly investigated except for the interaction between NOS3 and heat shock protein 90. 33 Our laboratory is currently attempting to establish which other components of this mechanism are involved in regulation of THAL NOS3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, activation and translocation of NOS 3 in the thick ascending limb have been reported to require heat shock protein 90 ATPase activity. 54 Phosphorylation of NOS 3 by protein kinase A was first reported in 2001. 55 However, not until NOS 3 activation by shear stress was shown to be mediated by phosphorylation of serine 1179 in endothelial cells 56 were the potential consequences appreciated.…”
Section: Regulation Of Nos Activitymentioning
confidence: 99%
“…Thus, in the absence of exogenously added L-arginine, thick ascending limbs do not generate NO (25). Several factors stimulate NO production in this nephron segment, including angiotensin (5,35), ␣-2 adrenergic agonists (31,45), endothelin (13,32), and luminal flow (28,29). Once generated, NO activates soluble guanylate cyclase and forms cGMP (21).…”
mentioning
confidence: 99%